lncRNA-Xist/miR-101-3p/KLF6/C/EBPα axis promotes TAM polarization to regulate cancer cell proliferation and migration - Yanyun Zhao; Zhaojin Yu; Rong Ma; Yifan Zhang; Lin Zhao; Yuanyuan Yan; Xuemei Lv; Liwen Zhang; Panpan Su; Jia Bi; Hong Xu; Miao He; et al. (Elsevier, 2021)
The phenotypic switch in tumor-associated macrophages (TAMs) mediates immunity escape of cancer. However, the underlying mechanisms in the TAM phenotypic switch have not been systematically elucidated. In this study, long noncoding RNA (lncRNA)-Xist, CCAAT/enhancer-binding protein (C/EBP)α, and Kruppel-like factor 6 (KLF6) were upregulated, whereas microRNA (miR)-101 was downregulated in M1 macrophages-type (M1). Knockdown of Xist or overexpression of miR-101 in M1 could induce M1-to-M2 macrophage-type (M2) conversion to promote cell proliferation and migration of breast and ovarian cancer by inhibiting C/EBPα and KLF6 expression. Furthermore, miR-101 could combine with both Xist and C/EBPα and KLF6 through the same microRNA response element (MRE) predicted by bioinformatics and verified by luciferase reporter assays. Moreover, we found that miR-101 knockdown restored the decreased M1 marker and the increased M2 marker expression and also reversed the promotion of proliferation and migration of human breast cancer cells (MCF-7) and human ovarian cancer (OV) cells caused by silencing Xist. Generally, the present study indicates that Xist could mediate macrophage polarization to affect cell proliferation and migration of breast and ovarian cancer by competing with miR-101 to regulate C/EBPα and KLF6 expression. The promotion of Xist expression in M1 macrophages and inhibition of miR-101 expression in M2 macrophages might play an important role in inhibiting breast and ovarian tumor proliferation and migration abilities.